Institutional Convergence of Bulgaria to the Eurozone Countries - Marikina, Maria (UNWE Yearbook, 2021)
Institutions are one of the main factors for the economic growth and development of any economy. And insofar as development is defined as a set of economic and institutional factors, the reduction of differences in the development of individual countries and regions naturally leads us to the institutional convergence, which is the object of study. When researching the convergence of Bulgaria to the EU countries and more closely to the Eurozone, many questions arise about whether there is institutional convergence and how it can be revealed. This is the subject of analysis presented in the study. The thesis presented here is that it is possible to consider institutional convergence for Bulgaria with the countries of the Euro zone, represented by qualitative and quantitative indicators, which, however, is unstable. The methodology is based on the understanding of institutional convergence as the converging of economic and political institutions, and given the fact that they are different for each of the economies; a comparative analysis is used to study the convergence as a whole. For this purpose, the analysis of institutional quality and comparative analysis uses the main indicators of the World Bank – Worldwide Governance Indicators (WGI) and Ease of Doing Business Indicator. The results of the pre-selected criteria give grounds to find those of the observed indicators, which reveal improvement and respectively converging in the direction of institutional convergence of Bulgaria with the countries from the EU area.
Keywords: Institutions; Institutional quality; Institutional convergence